Strategies to Apply Leadership Styles and Workloads to Hotel Employee’s Morale - Ni Luh Putu Sri Ratih Trisna Dewi; I Ketut Astawa; Nyoman Mastiani Nadra (International Journal of Glocal Tourism, 2020)
Purpose: This research aims to determine the effect of leadership style and workload partially or simultaneously on employee’s morale at 4 star hotel in Kuta tourist area, southern part of Bali, Indonesia. Research methods: The samples used were 34 respondents using proportionate stratified random sampling techniques. The data collection methods are questionnaires that have been tested for validity and reliability in advance and the analysis technique used is the Classic Assumption Test, T test, F test, Multiple Linear Regression Analysis and Coefficient of Determination Analysis. Findings: The leadership style and workload variables have a significant positive partial effect on employee morale and the leadership style and workload variables have a significant positive effect simultaneously on employee morale. Implication: The influence of the leadership style is quite large in increasing hotel employee morale.